Renaissance art and music (Chicago, Il Clearvue/eav, 1986)
Provides a general introduction to Renaissance art and music and describes the early Renaissance in Florence, Italy. Also deals with the early Renaissance in Rome, Venice, and other parts of Europe.
VHS format.
Writer, Ronald Konetchy.
Keywords: Art, Renaissance; Renaissance